Automation of strategy using IDEF0 — A proof of concept. (December 2015) - Waissi, Gary R.; Demir, Mustafa; Humble, Jane E.; Lev, Benjamin
Abstract: The goal of this interdisciplinary paper is to show that an existing modeling language, Integration Definition for Function Modeling (IDEF0), is applicable for use in strategy modeling and for automation of strategic plan development and implementation. We will show how utilization of the systems modeling language IDEF0 simplifies strategic plan development, and moves strategic planning and management from a static, document-based approach to a model- and software-based approach. A sequence of examples, as a proof-of-concept, is shown to demonstrate the use of IDEF0 to translate document-based strategic plans to model-based plans. The advantages of IDEF0 include: a well-tested language, and comprehensive systems modeling technique. The resulting IDEF0 models are well-defined, well-structured, easy to understand, easy to modify and use, and can be extended to any depth of detail. It is noted, that while the paper focuses on small- and medium manufacturing enterprises (SME), the approach can be used for strategy development and strategy automation of any size company or organization.